2020
DOI: 10.1093/function/zqaa013
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Inflammation Is Directly Linked to Obesity-Induced Insulin Resistance, while Gut Dysbiosis and Mitochondrial Dysfunction Are Not Required

Abstract: Obesity is associated with adipose tissue hypertrophy, systemic inflammation, mitochondrial dysfunction, and intestinal dysbiosis. Rodent models of high fat diet (HFD)-feeding or genetic deletion of multi-functional proteins involved in immunity and metabolism are often used to probe the aetiology of obesity; however, these models make it difficult to divorce the effects of obesity, diet composition, or immunity on endocrine regulation of blood glucose. We therefore investigated the importance of adipose infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Inflammation is associated with metabolic dysfunction such as obesity and insulin resistance [133]. Several studies suggest that obesity-associated, chronic, low-grade inflammation can cause insulin resistance in metabolic tissues like liver, muscle, and adipose tissues [134][135][136].…”
Section: Effects Of Hyperinsulinemia On Inflammationmentioning
confidence: 99%
“…Inflammation is associated with metabolic dysfunction such as obesity and insulin resistance [133]. Several studies suggest that obesity-associated, chronic, low-grade inflammation can cause insulin resistance in metabolic tissues like liver, muscle, and adipose tissues [134][135][136].…”
Section: Effects Of Hyperinsulinemia On Inflammationmentioning
confidence: 99%
“…Although evidence suggests a link between mitochondrial dysfunction and insulin resistance, dysfunctional mitochondria may not be necessary to induce insulin resistance in adipocytes. Recently, a study investigating the role of adipose inflammation, mitochondrial dysfunction, and gut dysbiosis in obesity‐induced insulin resistance, the authors found that mitochondrial dysfunction and gut dysbiosis occurred during HFD‐feeding but was not present in spontaneously obese mice (Petrick et al., 2020). This suggests that mitochondrial dysfunction may be diet‐related and is not always required for obesity‐induced insulin resistance.…”
Section: Adiposementioning
confidence: 99%
“…Many mechanistic studies examining the relationship between obesity and its associated chronic low‐grade inflammation have highlighted the role of pattern recognition receptors (PPRs), specifically Toll‐like receptors (TLRs) and Nucleotide‐binding oligomerization domain (NOD)‐like receptors or (NLRs), and their impact on insulin resistance (Petrick et al., 2020; Schertzer et al., 2011). Obesity is thought to provoke increased intestinal permeability, giving rise to higher circulating levels of lipopolysaccharide (LPS) emitted by intestinal gram‐negative bacterial species (Saad et al., 2016).…”
Section: Novel Mechanisms Of Cross‐talk Between Muscle Adipose and mentioning
confidence: 99%
“…Obesity, mainly caused by genetic and environmental factors, is a worldwide epidemic metabolic disease characterized by excessive fat accumulation. It not only affects body appearance but also contributes to many chronic inflammatory diseases, such as type 2 diabetes, hepatic steatosis and cardiovascular diseases (Petrick et al, 2020;Scheithauer et al, 2020;Agüera et al, 2021). However, the global prevalence of obesity is immensely high and alarming projections suggest that more than one billion people will be obese by 2030 (Kelly et al, 2008;Finucane et al, 2011).…”
Section: Introductionmentioning
confidence: 99%